Association between biopsychosocial factors and self-reported COVID-19 clinical complications in a Brazilian city - Murilo César do Nascimento; Silvana Maria Coelho Leite Fava; Eliza Maria Rezende Dázio; Simone Albino da Silva; Kênia Lara Silva; Alexandre Balsanuf Oliveira; Felipe Mendes Delpino; Inês Fronteira; Ricardo Alexandre Arcêncio; Namie Okino Sawada (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2022)
ABSTRACT Objective: This study aimed to analyze the existence of an association between the biopsychosocial profile of people affected and the number of self-reported clinical complications from COVID-19 in a Brazilian city. Methods: This is a cross-sectional (baseline) study, nested in a cohort study, carried out with 217 confirmed cases of COVID-19, interviewed from January to October 2021, during home visits, in a city in the south of Minas Gerais, Brazil. A structured questionnaire with the KoboToolbox resource was used. The independent variables were sociodemographic and clinical profile (comorbidities), quality of life, post-traumatic stress, anxiety, depression, and social support. The dependent variable was the number of self-reported clinical complications from COVID-19. The multivariate linear regression technique was adopted for the analyses. Results: The participants reported multiple clinical complications from COVID-19. There were "four or more" complications in 94.6% of the cases. Having a history of high blood pressure was associated with more complications post-SARS-CoV-2 infection, whereas having a caregiver and presenting with post-traumatic stress were associated with fewer COVID-19 complications. Conclusion: The multisystemic nature of the complications caused by COVID-19 and the associations identified emphasizes the need for an integrated approach to patients and for studies that monitor the effects of the disease on the demands placed on health systems, aiming to better understand and address them.